2006
DOI: 10.1038/ng1782
|View full text |Cite
|
Sign up to set email alerts
|

A common haplotype of interferon regulatory factor 5 (IRF5) regulates splicing and expression and is associated with increased risk of systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a complex autoimmune disease characterized by activation of the type I interferon (IFN) pathway. Here we convincingly replicate association of the IFN regulatory factor 5 (IRF5) rs2004640 T allele with SLE in four independent case-control cohorts (P = 4.4 x 10(-16)) and by family-based transmission disequilibrium test analysis (P = 0.0006). The rs2004640 T allele creates a 5' donor splice site in an alternate exon 1 of IRF5, allowing expression of several unique IRF5 isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
569
6
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 606 publications
(601 citation statements)
references
References 23 publications
25
569
6
1
Order By: Relevance
“…12,14,[17][18][19] Similar to African Americans, we again found the strongest associations at rs2004640 (P ¼ 2.2 Â 10 À9 ) and rs3807306 (P ¼ 3.0 Â 10 À9 ) in both OMRF and CASSLE and in both studies combined. Allele frequencies were similar to Caucasian populations previously reported (Table 2).…”
Section: Association Of Sle and Irf5 Variantssupporting
confidence: 64%
See 4 more Smart Citations
“…12,14,[17][18][19] Similar to African Americans, we again found the strongest associations at rs2004640 (P ¼ 2.2 Â 10 À9 ) and rs3807306 (P ¼ 3.0 Â 10 À9 ) in both OMRF and CASSLE and in both studies combined. Allele frequencies were similar to Caucasian populations previously reported (Table 2).…”
Section: Association Of Sle and Irf5 Variantssupporting
confidence: 64%
“…18 Since then, several additional studies have evaluated the association between IRF5 and SLE in Caucasian, [12][13][14]17,19 Korean 16 and Hispanic (Mexican) 15 populations, emphasizing the importance of this gene in SLE etiology. However, no studies have been reported to date in African Americans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations